Recent Progresses in Oxygen Reduction Reaction Electrocatalysts for Electrochemical Energy Applications - Li, Yahao; Li, Qingyu; Wang, Hongqiang; Zhang, Lei; Wilkinson, David P.; Zhang, Jiujun (Electrochemical energy reviews, 2019)
Electrochemical energy storage systems such as fuel cells and metal–air batteries can be used as clean power sources for electric vehicles. In these systems, one necessary reaction at the cathode is the catalysis of oxygen reduction reaction (ORR), which is the rate-determining factor affecting overall system performance. Therefore, to increase the rate of ORR for enhanced system performances, efficient electrocatalysts are essential. And although ORR electrocatalysts have been intensively explored and developed, significant breakthroughs have yet been achieved in terms of catalytic activity, stability, cost and associated electrochemical system performance. Based on this, this review will comprehensively present the recent progresses of ORR electrocatalysts, including precious metal catalysts, non-precious metal catalysts, single-atom catalysts and metal-free catalysts. In addition, major technical challenges are analyzed and possible future research directions to overcome these challenges are proposed to facilitate further research and development toward practical application. Graphic Abstract